The Bektashi miscellanea of Âşık Penâhî : sufi literature through the eyes of a poet-compiler - Çetinkaya, Ömercan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The subject of this thesis is the publication and content analysis of a miscellanea (Penâhî Mecmuası) completed by Mustafa Müslim Ocak (Penâhî) in 1902. The miscellanea contains the texts of Sufi poets and writers, especially figures of the Alevi-Bektashi tradition. In recent years, with the growing interest in this field in Ottoman literature, many miscellanies have been published, and their contents have been classified. This thesis, like its predecessors, applies the publication and classification methods used in miscellanea studies to the manuscript. However, in addition to this, this study asks new questions to miscellanies in terms of their compiler and content and introduces new perspectives to the field. This study consists of six chapters. The first chapter provides background about miscellanea literature, 19th-century reading practices, and the history of Sufism (especially in the context of the Bektashiyye). This section also introduces the compiler Penâhî and his miscellanea and other works. The second chapter includes the description of the manuscript, and a series of tables related to the manuscript's content. The third chapter focuses on Penahi's methods and purposes in copying texts and poems in his manuscript. Then the chapter discusses some specific examples in the manuscript to uncover the reading practices of the compiler. The fourth chapter examines the elements of belief and sufi teachings encountered in the poems and other mystical texts (most of which belong to the Alevi- Bektashi tradition). This section presents prominent themes in the sufi beliefs of Penâhî, as a minstrel and a compiler. After the fifth (conclusion) chapter, the sixth chapter gives the transliteration of the miscellanea.
Keywords: Penahi, Mustafa Müslim Ocak, 1847-1942.; Sufi poetry, Turkish.